Consequence of paradigm shift with repeat landscapes in reptiles: Powerful facilitators of chromosomal rearrangements for diversity and evolution (running title: Genomic impact of repeats on chromosomal dynamics in reptiles) - Ahmad, Syed Farhan; Singchat, Worapong; Jehangir, Maryam [UNESP]; Panthum, Thitipong; Srikulnath, Kornsorn (MDPI, 2020)
Reptiles are notable for the extensive genomic diversity and species richness among amniote classes, but there is nevertheless a need for detailed genome-scale studies. Although the monophyletic amniotes have recently been a focus of attention through an increasing number of genome sequencing projects, the abundant repetitive portion of the genome, termed the “repeatome”, remains poorly understood across different lineages. Consisting predominantly of transposable elements or mobile and satellite sequences, these repeat elements are considered crucial in causing chromosomal rearrangements that lead to genomic diversity and evolution. Here, we propose major repeat landscapes in representative reptilian species, highlighting their evolutionary dynamics and role in mediating chromosomal rearrangements. Distinct karyotype variability, which is typically a conspicuous feature of reptile genomes, is discussed, with a particular focus on rearrangements correlated with evolutionary reorganization of micro-and macrochromosomes and sex chromosomes. The exceptional karyotype variation and extreme genomic diversity of reptiles are used to test several hypotheses concerning genomic structure, function, and evolution.
Keywords: Amniote; Chromosome; Genome; Karyotype; Sex chromosome